Konsep Transformasi Struktural Pada Sektor Industri - Adela Wafiq Azizah; Muhammad Yasin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study discusses the structural transformation of the industrial sector in Indonesia, which has undergone significant changes in the past two decades. This transformation is characterized by a decline in employment in primary sectors such as agriculture, and an increase in secondary and tertiary sectors, such as manufacturing and trade. This study aims to analyze the impact of structural transformation in industry on employment, the influence of structural transformation in industry, and the role of government in industrial transformation. The research method involves secondary data analysis from various sources and case studies. The results show that government intervention, improvement of labor skills, collaboration between sectors, and strict environmental protection are the keys to successful sustainable industrial transformation. The implications of this research lead to more integrated and sustainable policy recommendations to support optimal structural transformation.